Annual risk of falls resulting in emergency department and hospital attendances for older people: an observational study of 781, 081 individuals living in Wales (United Kingdom) including deprivation, frailty and dementia diagnoses between 2010 and 2020. (2nd August 2022) - Hollinghurst, Robyn; Williams, Neil; Pedrick-Case, Rebecca; North, Laura; Long, Sara; Fry, Richard; Hollinghurst, Joe
Abstract: Background: falls are common in older people, but associations between falls, dementia and frailty are relatively unknown. The impact of the COVID-19 pandemic on falls admissions has not been studied. Aim: to investigate the impact of dementia, frailty, deprivation, previous falls and the differences between years for falls resulting in an emergency department (ED) or hospital admission. Study Design: longitudinal cross-sectional observational study. Setting: older people (aged 65+) resident in Wales between 1 January 2010 and 31 December 2020. Methods: we created a binary (yes/no) indicator for a fall resulting in an attendance to an ED, hospital or both, per person, per year. We analysed the outcomes using multilevel logistic and multinomial models. Results: we analysed a total of 5, 141, 244 person years of data from 781, 081 individuals. Fall admission rates were highest in 2012 (4.27%) and lowest in 2020 (4.27%). We found an increased odds ratio (OR [95% confidence interval]) of a fall admission for age (1.05 [1.05, 1.05] per year of age), people with dementia (2.03 [2.00, 2.06]) and people who had a previous fall (2.55 [2.51, 2.60]). Compared with fit individuals, those with frailty had ORs of 1.60 [1.58, 1.62], 2.24 [2.21, 2.28] and 2.94 [2.89, 3.00] for mild, moderate and severe frailty respectively. Reduced odds were observed for males (0.73 [0.73, 0.74]) and less deprived areas; most deprived compared with least OR 0.75 [0.74, 0.76]. Conclusions: falls prevention should be targeted to those at highest risk, and investigations into the reduction in admissions in 2020 is warranted.